PENGARUH PEMBERIAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA DAN LOYALITAS KARYAWAN - Sri Hariyanti (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2020)
The role of human resources in a company is very important and is one of the determining factors for a company's success. Therefore it must be empowered as best as possible to be able to provide optimal output. It is as if the symbiosis of mutualism between the company and the workers because basically, everyone will work to get rewards for the efforts they have made to achieve the company's targets. There are 2 types of compensation, financial compensation and non- financial compensation. Financial compensation has been determined according to the regional minimum wage where the company is located and it is very possible that the standard salary / financial compensation between one company and another is the same. But the kind and type of non-financial compensation for each company can be different because it depends on the policies and capabilities of the company also and it can be a special competitiveness for companies to increase employee motivation, then if employee motivation is high then automatically employee performance and loyalty will also increase. it means that non-financial compensation indirectly affects employee performance and loyalty.